Researchers’ perceptions of ethical challenges in cluster randomized trials: a qualitative analysis - McRae Andrew D; Bennett Carol; Brown Judith Belle; Weijer Charles; Boruch Robert; Brehaut Jamie; Chaudhry Shazia; Donner Allan; Eccles Martin; Grimshaw Jeremy; Zwarenstein Merrick; Taljaard Monica (Trials, 2013)
Abstract Background Cluster randomized trials (CRTs) pose ethical challenges for investigators and ethics committees. This study describes the views and experiences of CRT researchers with respect to: (1) ethical challenges in CRTs; (2) the ethics review process for CRTs; and (3) the need for comprehensive ethics guidelines for CRTs. Methods Descriptive qualitative analysis of interviews conducted with a purposive sample of 20 experienced CRT researchers. Results Informants expressed concern over the potential for bias that may result from requirements to obtain informed consent from research participants in CRTs. Informants suggested that the need for informed consent ought to be related to the type of intervention under study in a CRT. Informants rarely expressed concern regarding risks to research participants in CRTs, other than risks to privacy. Important issues identified in the research ethics literature, including fair subject selection and other justice issues, were not mentioned by informants. The ethics review process has had positive and negative impacts on CRT conduct. Informants stated that variability in ethics review between jurisdictions, and increasingly stringent ethics review in recent years, have hampered their ability to conduct CRTs. Many informants said that comprehensive ethics guidelines for CRTs would be helpful to researchers and research ethics committees. Conclusions Informants identified key ethical challenges in the conduct of CRTs, specifically relating to identifying subjects, seeking informed consent, and the use of gatekeepers. These data have since been used to identify topics for in-depth ethical analysis and to guide the development of comprehensive ethics guidelines for CRTs.